The protective effects of golden berry (Physalis peruviana L.) extract against to the oxidative and destructive effects of type i diabetes in rats - Erman, Fazilet; Kaya, Tubay; Aydin, Sevinc; Erman, Orhan; Yilmaz, Okkes (Parlar Scientific Publications, 2020)
Type I diabetes is known as insulin-dependent diabetes mellitus, and the most important factor playing role in its formation is the genetic predispo- sition. Physalis peruviana L. (Goldenberry) is a plant, which has strong antioxidant properties, from Solanaceae family and, because of its fructose con- tent, plays regulatory role in blood glucose level of diabetics. In this study, it has been investigated the effects of goldenberry on the malondialdehyde (MDA), reduced glutathione (GSH), total protein, vitamins A, D, E, and K, and cholesterol levels which are the indicators of antioxidant defense and the oxidative damages in serum, muscle, kidney, liver and brain tissues of the rats, on which type I diabetes was induced by STZ. According to the obtained results, among the rats with STZ-induced type I diabetes, it was ob- served that the level of glutathione (GSH) increased and the level of malondialdehyde (MDA) decreased in all of the tissues of rats given goldenberry extract, while significant decreases were determined in the levels of vitamins K-1, K-2, D-2 and D-3 in all of tissues (except serum), and there were also decreases in the level of ?-tocopherol and cholesterol in tis- sues of muscle, liver and kidney. In this study, it was shown that the goldenberry decreased the destructive effects of type-I diabetes by decreasing the serum glucose and lipid peroxida- tion and increasing the level of glutathione. It is believed that the obtained results would be used in fol- low-up of diabetic patients and in early diagnosis of the disease in future. © by PSP.
Keywords: Goldenberry (Physalis peruviana L.); GSH; Lipid peroxidation (LPO); MDA; Vitamin